2D Photocatalyst System of Mn3O4:Ag Nanocomposite to the Degradation of Methylene Blue Under Solar Light - Salman , Rawaa H.; Abdul Karem, Lekaa K.; Khalil, Ahmed M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
Constructing two-dimensional (2D) composites using layered materials is considered a practical approach to achieving high-efficiency photocatalysts. This study aims to prepare manganese oxide nanoparticles (NPs) from the aqueous extract of thyme leaves, characterize them by spectroscopic methods, and bridge the gap by developing an environmentally friendly, photostable coating and evaluating its efficiency in degrading the methylene blue (MB) dye under sunlight, suitable for practical water treatment applications. In this work, a 2D nano-photocatalytic coating of Mn3O4:Ag was developed for the efficient removal of organics and pollutants from water under sunlight. The method involves synthesizing a photocatalytic nanomaterial via green synthesis of a Mn3O4/Ag nanocomposite using thyme leaf extract. The products were characterized using X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The image of the Mn3O4: Ag nanocomposite showed spherical NPs with extensive aggregation. The average crystal size was calculated to be 23.7 nm using the Debye-Scherrer equation, and the crystals were incorporated into a white, waterproof coating to produce a homogeneous nano-coating. The final product is applied to solid surfaces and dried at room temperature. The resulting layer demonstrates high efficiency in degrading the MB dye, a model pollutant. The system is eco-friendly, cost-effective, and suitable for water treatment applications. The advantage of this work is the use of green synthesis to produce Mn3O4:Ag nanocomposite, which is incorporated into a coating that serves as a photocatalytic layer under sunlight, making it suitable for environmental remediation applications.